IDENTFIKASI KUALITAS PRODUK INDUSTRI KERAJINAN LILIN: STUDI KASUS PADA PRODUK LILIN AROMATERAPI SEBAGAI PENGHARUM RUANGAN DAN AROMA RELAKSASI UMKM NATURELINE BOYOLALI - Wahid, Satriya Nur; Hasmarini, Maulidyah Indira (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
Indonesia's aromatherapy candle market is expanding quickly in response to consumer desire for goods that promote both aesthetic and relaxing advantages. The purpose of this study is to examine the variables that affect the quality of aromatherapy candles, including the type of essential oil, wick, container, and raw material selection. Choosing premium essential oils adds to the longevity and potency of the scent, while candles made of palm, soy, or beeswax wax have an edge over paraffin in terms of burn resistance. In addition, this study addresses the safety of candle containers, pointing out that while using glass containers adds aesthetic appeal, they run the risk of shattering from too much heat. As an alternative, eco-friendly materials like wood or coconut shells might be a creative way to improve the sustainability of a product. Given growing consumer knowledge of eco-friendly products and the advantages of aromatherapy, aromatherapy candles have a tremendous chance to compete in both domestic and international markets with innovative materials, designs, and marketing strategies.